Meta-Analysis the Effect of Screen Time on the Risk of Overweight in Children and Adolescents in Asia - Nita Putriasti Mayarestya; Eti Poncorini Pamungkasari; Hanung Prasetya (Journal of Health Promotion and Behavior, 2021)
Background: Overweight and obesity are a growing threat to the well-being of the world's children. In 2010-2016, the prevalence of underweight was growing rapidly among children and adolescents in Asia. With the development of technology, screen time has become a behavior that can have a negative effect on children and adolescents if it is associated with being overweight. One in three internet users in the world are children and adolescents under the age of 18 years. Asia has the highest rates of child internet use globally. Several studies in Asian countries reported high screen time in children and adolescents. On average, children and adolescents in Asia have screen time duration > 2 hours per day outside of study/school time. This study aims to analyze the effect of screen time duration on overweight children and adolescents in Asia.Subjects and Method: This research is a systematic review and meta-analysis conducted using PRISMA flow diagrams. Search articles through journal databases including: Google Schoolar, Science Direct, Researchgate and PubMed by selecting articles published in 2010-2021. “Screen Time” OR “Sedentary Behavior” AND “Overweight” OR “Body Mass Index” OR “BMI” OR “Weight” OR “Obesity” AND “Children” OR “Child” OR “Adolescent” OR “Teen” AND “Cross Sectional". Inclusion criteria were articles using English or Indonesian, full paper articles with cross sectional design, 5-19 years old sample, screen time duration > 2 hours per day, research locations in Asia. Eligible articles were analyzed using the Revman 5.3 application.Results: A meta-analysis of 11 cross-sectional articles concluded that children and adolescents with screen time duration > 2 hours per day had a 1.63 times greater risk of being overweight than children and adolescents with screen time duration 2 hours (aOR = 1.63; 95% CI = 1.13). up to 2.35; p=0.009).Conclusion: Children and adolescents with screen time duration > 2 hours per day are at risk of being overweight.Keywords: Screen time, overweight Correspondence:Nita Putriasti Mayarestya. Masters Program in Public Health. Universitas Sebelas Maret, Jl.Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: nmayarestya@gmail.com Mobile: 085252493555.Journal of Health Promotion and Behavior (2021), 06(03): 201-211DOI: https://doi.org/10.26911/thejhpb.2021.06.03.04